Understanding carbon-biomolecules interactions for the rational design of carbon-based biomaterials - VASCONCELOS, JOANA MARTA (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
Carbon-based materials have shown an outstanding performance in the biomedical field and the desire of understanding the impressive bioresponse towards carbon materials is an attractive prospect for design of improved biomaterials. Carbon performance in vivo is thought to depend on the composition/structure of an initially adsorbed protein/lipid layer; however, there is still a great controversy regarding the structure of the adsorbed layer and the role of this layer in the long-term bioresponse towards carbon-based biodevices. This thesis aims to contribute to a fundamental understanding on the interactions of carbon thin films with model lipid assemblies and on the influence of carbon/lipid interactions on the long-term performance of carbon coatings. Firstly, a detailed description on the physico-chemical properties of amorphous carbon (a-C) films used in this thesis is presented. Bare amorphous carbon (a-C), oxidised amorphous carbon (a-C:O) and hydrogen doped amorphous carbon (a-C:H) are characterised with regards to their surface morphology, chemistry, wettability and charge. Results suggest increasing graphitic content in the order a-C:H < a-C:O < a-C. The wettability of carbon films is found to increase in the order a-C:H < a-C < a-C:O, alongside the oxygen content of those films. Determinations of surface ζ-potential yield isoelectric points of pHiso = 3.0-3.7 and pHiso < 1.5 for a-C and a-C:O surfaces, respectively. Secondly, phospholipid liposomes are utilised as model lipid aggregates and their size and electrostatic stability are studied regarding preparation method, nature and type of phospholipids present in the liposome. Phosphatidylcholine (PC) and phosphatidylserine (PS) are combined in 80:20 PC/PS liposomes, a similar ratio to that found in biological media. PC/PS liposomes are found to be electrostatically stable and homogeneously dispersed at all buffer conditions. Ex-situ and in-situ studies on PC/PS liposome adsorption on carbon surfaces are performed by using a combination of microscopic, spectroscopic and nanogravimetric techniques. Ex-situ results indicate that liposomes adsorb at a-C surfaces independent of the buffer being used. Liposome adsorption at a-C:O surfaces, however, is only observed when Ca2+ is added to the buffer. Further in-situ measurements confirm ex-situ observations and suggest that liposome adsorption on both a-C and a-C:O surfaces is made through intact vesicle adsorption at the interface, except under conditions that promote liposome rupture. Finally, the long-term bioresponse towards carbon films is investigated by studying the effect of surface properties on the cellular compatibility of carbon thin films. Results indicate that the adhesion of endothelial and fibroblast cells at carbon surfaces is slightly reduced in a-C:O, when compared to a-C. Additionally, the anti-thrombogenic and anti-fungal behaviours of carbon films is studied. Oxidised carbon shows a significant decrease in platelet and fungi adhesion and spreading when compared with a-C, which is attributed to the high hydrophilicity of a-C:O surfaces. These results show the potential of carbon films for biomedical applications and highlight carbon's performance as a biomaterial with the unique combination of high biocompatibility, anti-thrombogenic and anti-fungal behaviours.
APPROVED
Keywords: amorphous carbon; bioresponse; lipid/carbon interactions